2013
DOI: 10.1016/b978-0-12-407707-2.00002-3
|View full text |Cite
|
Sign up to set email alerts
|

Residual Immune Dysregulation Syndrome in Treated HIV infection

Abstract: Antiretroviral therapy has revolutionized the course of HIV infection, improving immune function and decreasing dramatically the mortality and morbidity due to the opportunistic complications of the disease. Nonetheless, even with sustained suppression of HIV replication, many HIV-infected persons experience a syndrome characterized by increased T cell activation and evidence of heightened inflammation and coagulation. This residual immune dysregulation syndrome or RIDS is more common in persons who fail to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
278
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 308 publications
(291 citation statements)
references
References 177 publications
(240 reference statements)
10
278
1
2
Order By: Relevance
“…Indices of inflammation and coagulation are heightened in ART-suppressed HIV-infected persons, particularly in patients with suboptimal CD4 + T-cell reconstitution [39,40], and these indices predict cardiovascular risk [41,42]. Circulating immune cells can interact with soluble coagulation elements through expression of the thrombin receptor PAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…Indices of inflammation and coagulation are heightened in ART-suppressed HIV-infected persons, particularly in patients with suboptimal CD4 + T-cell reconstitution [39,40], and these indices predict cardiovascular risk [41,42]. Circulating immune cells can interact with soluble coagulation elements through expression of the thrombin receptor PAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible etiologies for the suboptimal vaccine response seen in adults with well-controlled HIV infection include residual immune dysfunction from the initial HIV infection, and/or chronic immune activation from HIV infection itself. 33 In addition, the CD4 count normal range, generally defined as 500-1500 cells/mm 3 , may be too broad. A recent study found that the median CD4 count in HIV-uninfected subjects was 900 cells/mm 3 , and that HIV-infected subjects who started antiretroviral therapy earlier were both more likely to achieve CD4 counts >900 cells/mm 3 , and more likely to respond to HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In humanised mice, the human IFN-α14 subtype was more potent than IFN-α2 in antiviral activity when used in postexposure prophylaxis and treatment of acute viral infection with better regulation of immune hyperactivation [55]. Distinct from IFN-α2, which elicited higher As seen in the clinical HIV-1 setting, systemic immune activation via IFN stimulation of monocytes is a hallmark characteristic regardless of successful anti-retroviral treatment in suppressing plasma levels of HIV RNA [56,57]. In fact, HIV-1-induced immune hyperactivation is associated with increased prevalence and earlier onset of co-morbidities (cognitive decline, diabetes, liver disease, cardiovascular disease), signifying disease progression in HIV-1 patients.…”
Section: Human Immunodeficiency Virus-1mentioning
confidence: 99%